Kooperative Planung und Steuerung in logistischen Netzwerken - Mertin, Marcel (Wissenschaftliche Berichte des Instituts für Fördertechnik und Logistiksysteme des Karlsruher Instituts für Technologie, 2021)
This work examines the causes and consequences of volatility in the regular processes of a logistic network. On the basis of the findings, a concept for cooperative planning and control using software agents is proposed and evaluated in a simulation environment in comparison to a sequence control based on the FIFO principle. The focus is on examining the effectiveness of a dynamic urgency assessment for prioritizing orders.